Puhe runoilija Archiaan puolustukseksi - Cicero, Marcus Tullius, 107 BCE-44 BCE; Hidén, K. J. (Karl Julius), 1867- (Salt Lake City, UT : Project Gutenberg, 2018)
"Puhe runoilija Archiaan puolustukseksi" by Marcus Tullius Cicero is a classical oration written in the 1st century BC. This work falls under the genre of legal rhetoric, and it serves as Cicero s defense of the poet Archias, who was accused of unlawfully claiming Roman citizenship. Cicero's eloquent discourse highlights the intersection of art, culture, and citizenship in Ancient Rome, illustrating the significance of intellectual contributions to society. In this defense speech, Cicero argues that Archias, a celebrated poet with roots in Antiochia, is deserving of Roman citizenship due to his literary contributions and the esteem in which he is held by prominent figures. He contends that the arts play a vital role in enhancing the glory of the Roman state and that Archias has brought honor through his poetry, which engages with themes of valor and patriotism. Cicero refutes the accusations against Archias, demonstrating his legitimate claim to citizenship through various legal frameworks and societal recognition, ultimately convincing the court to acquit Archias and affirming the importance of poetry in Roman culture. (This is an automatically generated summary.)
Release date is 2018-05-12
E-text prepared by Tapio Riikonen
Keywords: Rhetoric, Ancient; Oratory, Ancient; Archias, Aulus Licinius, 120 B.C.- -- Trials, litigation, etc; Trials -- Italy -- Rome; Citizenship -- Rome; Speeches, addresses, etc., Latin -- Translations into Finnish